Acute infectious diseases and immunologic responses. Some stories from clinical practice apropos the Influenza A (H1N1) pandemic - Alfredo Darío Espinosa Brito (Medisur)
Apropos of the appearance of some unusual clinical pictures in the course of the recent epidemic of Influenza A (H1N1), and with the intention of sharing controversial ideas related to the immunologic responses of the patients to the infectious agents, we expose here a group of stories arisen from a clinical practice of almost five decades.